(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Objective: Neuropharmacological effects of various extracts made from Naringi crenulata (Roxb.) Nicolson Leaves is the main objective of this stdy Materials and methods: The leaves used to authenticate Naringi crenulata (Roxb.) were sourced from Wayanad in Kerala. Throughout the extraction procedure, higher polarity solvents such petroleum ether, chloroform, and methanol were utilised.